Clinical efficacy of botulinum toxin type A reconstituted and refrigerated 1 week before its application in external canthus dynamic lines (2007)
BACKGROUND: Allergan Inc. recommends that its botulinum toxin type A (BTX-A; BOTOX) must be refrigerated and applied within 4 hours after its reconstitution to avoid losing its biologic effectiveness. OBJECTIVE: The objective was to compare clinical efficacy in treating external canthus dynamic lines with reconstituted and refrigerated toxin (BTX-A) 1 week before its application versus fresh toxin (BTX-A). METHODS: This study was a double-blind, randomized, clinical trial. A total of 30 patients aged 30 to 60 years having a minimum of one and maximum of six external canthus dynamic lines were treated in one canthus with 15 U of BTX-A reconstituted and refrigerated at 4°C 1 week before being applied and in the other with 15 U of fresh BTX-A. Patients were followed-up on Day 10 and Weeks 6, 12, and 18; assessment included a neuroconduction study of the facial nerve and the investigators' photographic evaluation of the number of external canthus dynamic lines at maximum smile. RESULTS: Outcome measurement did not show statistically significant differences between both groups. CONCLUSION: BTX-A, reconstituted and refrigerated 1 week before its application, has similar clinical efficacy in treating external canthus dynamic lines as does fresh BTX-A. © 2007 by the American Society for Dermatologic Surgery, Inc.